ATTITUDE OF CHAUVINIST: HADITH PERSPECTIVE IN THE ERA OF SOCIETY 5.0 AT JENDERAL SUDIRMAN UNIVERSITY - Didik Suwarno; Sustanto Sustanto; Naqiyah Naqiyah (Penerbit Lafadz Jaya, 2023)
The era of society 5.0 that simplifies human life brings culture from outside that erodes the attitude of love for the motherland. The research method uses qualitative methods and descriptive approaches with informant sources of Jenderal Sudirman University students. Qualitative methods are often called naturalistic research methods because the research is carried out on natural conditions. The results of this study are: 1. As the next generation of the nation, it is most important to show an attitude of chauvinistby studying hard as a form of defending the Indonesian nation from ignorance. 2. Using and purchasing domestic products. 3. Get to know Indonesian culture and introduce it to the international world. 4. Bringing Indonesia's name to the international world by participating in a number of competitions. Love of the homeland is a feeling that grows from one's heart to serve, maintain, defend, and protect the water from all threats and disturbances, while in the Islamic perspective it is contained in QS. Al-Hujarat verse 13. The cultivation of the character of chauvinistis carried out from an early age both in the family environment and in the university environment.